Mercury in Old Uyghur - Hacer Tokyürek (Türkiyat Mecmuası)
Mercury, accepted as a harmful chemical today, is widely used in many fields by various nations as it was used in ancient times. Nations who believed in this element’s changing and transforming properties believed that it transformed worthless metals into gold, a precious metal, and thus placed mercury in an important place in alchemy. In addition, mercury, which has an essential place in the science of medicine, has been combined with various plants or mixture included in drug compositions and used for therapeutic purposes. Mercury, used in Āyurvedic medicine, especially Indian medicine, is also included in yogic practice, considered among the sub-branches of Āyurveda. When the Old Uyghur texts are examined, the words that mean ‘mercury’, which appear in two different ways as könä suvı ‘mercury’ and zımıg ‘mercury’, are also used to transform worthless metals into gold, as well as to transform a worthless human into a divine body, as stated above. In addition, mercury is also included in various drug components for different purposes in medicine. This article aims to determine the words used for mercury in Old Uyghur, and the meanings and purposes of these words. Again, to show the reading differences in the text, and the movement over the read texts, the original texts are given in the article, and the text is transliterated again. So, the differences in reading and interpretation are reflected in the text.